Effects of Soils on the Morphology of the “nyù”, Yams of the Passoré in Burkina Faso - Tiama, Djakaridia; OUEDRAOGO, N.H.; YOLOU, M.; SAWADOGO, N.; BATIONO / KANDO, P.; ZOUNDJIHEKPON, JEANNE; SAWADOGO, M.; ZONGO, J.D. (My University, 2019)
This study aims at finding a concise understanding of the different modifications of the “nyù” noticed during the harvest. It specifically intends to give the effect of each type of soil on the morphology of the yam and on the choice of the producers. The results of this study shows that sandy soils produce tubers mostly appreciated with their filiform shape characterizing the “nyù”. As to the studied variables (Length, Diameter and Weight of the tuber), any significant difference has not been observed.
Keywords: Tuber; Crop; Mineral; Organic; fertilization; Ridges; Morphology